The days : his autobiography in three parts - Ḥusayn, Ṭāhā, 1889-1973 (The American University in Cairo, 2014)
For the first time, the three-part autobiography of one of modern Egypt's greatest writers and thinkers is available in a single paperback volume. The first part, An Egyptian Childhood (1929), is full of the sounds and smells of rural Egypt. It tells of Hussein's childhood and early education in a small village in Upper Egypt, as he learns not only to come to terms with his blindness but to excel in spite of it and win a place at the prestigious Azhar University in Cairo. The second part, The Stream of Days: A Student at the Azhar (1939), is an enthralling picture of student life in Egypt in t.